'Fernando Pessoa,' a document not by Fernando Pessoa - Freitas, Filipa de (Pessoa Plural, 2015)
Here we present a typed and unsigned document found among the papers that constitute the literary estate of Manuela Nogueira, the niece of Fernando Pessoa. The text, an essay on Fernando Pessoa and his heteronymism, includes reflections on the heteronyms Alberto Caeiro, Álvaro de Campos and, to a lesser degree, Ricardo Reis. It also offers English translations of poems signed by Pessoa, Campos and Caeiro. Preceding the facsimile and transcription, an introduction analyzes characteristics of the document that point to Hubert Jennings as its author.